A chemical analysis method to identify the source of pellicle adhesive contaminants. (10th April 2014) - Penley, C.; Guenther, T.; Walker, M.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; Hong, Tae Eun
<x xml:space="preserve">Abstract</x> Advanced lithography requirements have driven pellicle suppliers to develop improvements in both structure and materials. For example, thinner pellicle membranes now improve transmission of light, shortened aluminum frames now reduce image shadowing and advanced adhesives now reduce outgassing. The quality control and evaluative techniques employed to develop and monitor these improvements include ion chromatography (for cation and anion), gas chromatography–mass spectrometry (for organic volatile and semi‐volatile compounds) and ultraviolet–visible spectroscopy (for film transmission). As pellicle materials continue to evolve and diversify, additional analysis methods are essential to solve problems both in the development and semiconductor manufacturing phases. This paper summarizes a body of work that was completed in a manufacturing environment in response to an ongoing contamination issue ultimately traced to a particular KrF pellicle supplier. This contamination adversely impacted subsequent pellicles and photomasks undergoing the pellicle demounting process. In an attempt to identify the root source of the contamination, pellicles exhibiting successful demounting characteristics were compared to those that induced unacceptable contamination levels. Direct chemical analysis of respective mounting adhesives via time‐of‐flight secondary ion mass spectrometry identified mixtures of chemical components unique to each adhesive formulation. This information was fed back to the pellicle vendor who ultimately acknowledged an adhesive formulation change from a styrene‐type to an acryl‐type compound, after which the resulting pellicle product quality was verified and led to the return of contamination levels to within acceptable limits. Copyright © 2014 John Wiley & Sons, Ltd.